Terapi Komplementer Relaksasi Otot Progresif Jacobson Untuk Menurunkan Tekanan Darah Pada Penderita Hipertensi - Diah Ratnawati; Rosiana Rosiana (Poltekkes Kemenkes Surakarta, 2020)
Background: Hypertension is a condition of an increase in blood pressure from the normal range of 120/80 mmHg. If there is no action is taken to reduce blood pressure, it can lead to serious complications. Jacobson’s progressive muscle relaxation can be used as an action in reducing high blood pressure. Aims of this study is to analize effect of Jacobson’s progressive muscle relaxation to decrease blood pressure. Methods: This research used a quasi-experimental method and a sample of 16 respondents. JPMR Therapy is carried out for three weeks with three times each week. The action is carried out for 30 minutes. Blood pressure measured by spyghnomanometer before and after intervention. Results: the result of this intervention showed a P-Value is 0,0001, which means blood pressure decreases after intervention. Conclusions: This intervention is proven to be a complementary therapy for hypertension suffers. For this intervention to have the maximum results for blood pressure reduction, patients must routinely intervene every day along with the ingestion of the drug. The need for more research is how long normal blood pressure persists with JPMR.